Resolución de conflictos en la escuela : una herramienta para la cultura de paz y la convivencia - Silvina Funes Lapponi (Universidad de La Rioja, 2013)
The creation of a peaceful environment in living together at the educational centers through the promotion of specific social abilities, like better communication, negotiation and mediation, is an effective way to make an efficient peace education by the daily living together, and not only for a simple enunciation of facts or statements of principles, which usually are considered by students like a part of their curriculum. In peace culture related with our daily coexistence, conflict has to be seen as an opportunity of personal and group growing up, and not like simple problems of discipline that have to be solved one way or another. Considering this perspective, peace education means a peace in our daily living together, in resolving small degree conflicts, or in other way it means, an active peace, with solutions and constructive contributions as the main rol of the participants.